Some psychological characteristics of elite handball players in correlation with players' motor abilities - Bon, M.; Kajtna, T.; Sesum, A. (Kinesiologia Slovenica, 2020)
Personality characteristics, problem-solving, movement speed, explosive leg power and correlations between them are essential topics in elite handball, although studies in these fields are relatively rare. The correlations between psychological characteristics, problem-solving abilities, and some motor abilities in two different age categories were researched. The sample included 41 female handball players, 24 of which were members of the senior national team, with an average age of 24.79 years (SD = 4.84 years), and 17 girls from the Slovenian youth national team, whose average age was 16.35 (SD = 0.70 years). The differences in age between groups were statistically significant (t = 8.42, p (t) = 0.00). Players\' psychological characteristics were examined with the Wartegg test, while the Runs Test (different sprints and vertical jumps) was used to assess players` motor abilities. Identity has a significant negative (-0.61) correlation to CMJ - youth players with a lower identity score jumped higher. Furthermore, rational-emotional integrity is also negatively correlated to CMJ (0.58). Results do not conclusively describe the correlation between problem-solving and movement speed among female handball players. No any statistically significant differences between youth and senior players were discovered. The test results are an essential contribution to a better understanding of the correlation between specific psychological characteristics and problem-solving in relation to movement speed and explosive leg power of youth and senior female elite handball players despite the fact that the correlations were not statistically significant. However, this was the first use of the Wartegg test in female handball.